The FLEGT Initiative in Indonesia: implementation, achievements, challenges - Bednarska, Wiktoria; Gralewska, Daria (Destined to Cooperate? Various Dimensions of European Union Policy Towards Asian Countries, 2024)
In recent years, Indonesia has emerged as a leader in Southeast Asia in combating greenhouse gas emissions. However, despite being rich in natural resources such as tropical forests, the country still struggles with ongoing environmental degradation. Illegal logging and sustainable forest management have become particularly significant issues. The European Union and Indonesia collaborate in this regard through the FLEGT program. The aim of this chapter is to present and address questions regarding the practical implementation of FLEGT in Indonesia, the positive effects of cooperation achieved, as well as the challenges that the EU and the Indonesian government still need to overcome. The chapter will provide an overview of the FLEGT program, its implementation history in Indonesia, as well as the key controversies and challenges involved.